Clinical Outcome of Epilepsy Surgery of The Temporal Lobe in Paediatric Group: A Retrospective Cohort Study - Mohd Mispan, Mohd Khairun; Alias, Azmi; Mohamed, Ahmad Rithauddin; Kassim, Fauziah; Mat Said, Normawati; Abdullah, Jafri Malin (Malaysian Journal of Medical Sciences, 2025)
Background: This study was to identify seizure outcome following epilepsy surgery in paediatric group using Engel classification. We also identified histological and radiological findings of the study population. Methods: This study was a retrospective cohort study over a period of eight years from 1 January 2012 until 1 July 2019. Engel Outcome Classification was used to identify seizure outcome at immediate, three to six months and one year post-operation. Age, sex, age of seizure onset, age of operation, body weight, number of antiepileptic medications pre and post-operation, duration of stay in intensive care unit (ICU) and ward, magnetic resonance imaging (MRI) and histopathological findings and complications were noted. Analytically, Fisher’s exact test was used for categorical data. Wilcoxon Signed Rank test was used for continuous but not normally distributed data. In this study, Univariate logistic regression is used to understand whether Engel Classification I can be predicted from categorical variables and numerical variables. A set P-value of < 0.05 was considered of statistical significant. Results: 29 paediatric patients met study criteria. The mean time between seizure onset and surgery was 5.6 years. Non-invasive evaluation was used in all 29 patients during preoperative assessment. With the use of the Engel Outcome Classification, Engel I outcome or seizure free was achieved in 28 patients (96.6%) at immediate follow-up, 24 patients (82.8%) at three to six months follow-up and 24 (82.8%) at one year follow-up. Hippocampal Sclerosis was present in 13 patients (44.8%). Tumours were present in 16 patients (55.2%). The complication proportion was 14.4%. Only two patients (6.9%) underwent reoperations. There are significant changes in post operative Anti Epileptic Medications (AEDs) reduction in this study (P = 0.006). Possible risk factor of seizure was suggestive for less recurrence of seizure, which may become a predictor to achieve Engel I classification in this study (P = 0.052). Conclusion: The surgery outcome of epilepsy surgery of the temporal lobe in paediatric group was comparable in this study. Careful patient selection by multidisciplinary evaluations is mandatory.